TEACHERS’ STRATEGIES TO INCREASE VOCABULARY’S FOR YOUNG LEARNERS: TEACHERS’ USE AND PERCEPTION - Syahabuddin, Khairiah; Khasinah, Siti; Sa’i, Sa’i; Munawwarah, Munawwarah (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
Teaching English vocabulary to young learners is an essential component of early language education, serving as a cornerstone for building effective communication skills, fostering cognitive development, and enabling academic success. Studies on strategies teachers use and their perception on the effectiveness of the strategies they implement towards the teaching of vocabulary to young learners are still scarce. The purpose of this study was to examine the methods used by teachers to teach words/vocabulary to young students in English and to ascertain how these methods were perceived by the teachers themselves. A qualitative method was employed to seek answers. This study used interviews and observation as its instruments. Four teachers with a degree in English education who have been teaching young students in the language for more than a year made up the research participants. The results revealed that the teachers used games, pictures, memorizing techniques, translations, realia, action/mime/gesture, and songs. The teachers felt that various techniques were appropriate for teaching vocabulary to younger students since the teachers could combine more than two strategies in a single session. As a result, they used a variety of techniques and activities in their instructions to help young students enjoy studying English vocabulary.